Nationwide analysis of short-term surgical outcomes of minimally invasive esophagectomy for malignancy. (January 2016) - Thirunavukarasu, Pragatheeshwar; Gabriel, Emmanuel; Attwood, Kristopher; Kukar, Moshim; Hochwald, Steven N.; Nurkin, Steven J.
Abstract: Background: Minimally invasive esophagectomy (MIE) is being increasingly utilized for esophageal cancer. It is unclear if MIE if being safely performed with satisfactory outcomes across the USA. We aimed to analyze the short-term surgical outcomes of MIE as compared to open esophagectomy (OE). Methods: The National Cancer Database (NCDB) was queried for patients who underwent MIE or OE for esophageal malignancy between 2010 and 2011. Margin positivity, lymph node retrieval, 30-day mortality, 30-day unplanned readmission rate and hospital length of stay. Results: A total of 4047 patients were identified; 3050 (75.4%) underwent OE, and 997 (24.6%) underwent MIE. The proportion of MIE increased from 21.9% in 2010 to 27.4% in 2011 (p < 0.001). The conversion rate was 13.7%. There were no differences in-patient or tumor characteristics between the two cohorts. OE and MIE were comparable in terms of margin positive resection rate (7.4% vs. 8.1%, p = 0.48), 30-day unplanned readmission rate (7.6% vs. 7.2%, p = 0.64) and 30-day mortality rate (4.3% vs. 3.3%, p = 0.71). Compared to OE, MIE was associated with higher node retrieval (median 12 vs 14, p < 0.001), and shorter hospital stay (median 11.0 vs 10.0 days, p < 0.001). Logistic regression analysis showed that surgical approach (OE vs MIE) was not associated with 30-day mortality rate. In an ANCOVA analysis, MIE was independently associated with a shorter hospital stay compared to OE (estimated mean difference 1.57 ± 0.53 days, p = 0.003). MIE patients who underwent conversion had a longer hospital stay compared to those who did not (11.0 vs 10.0 days, p = 0.02). Conclusion: MIE is being offered more frequently to patients with esophageal cancer, and maybe accompanied with better short-term outcomes including shorter hospital stay when compared to open esophagectomy. Highlights: Minimally invasive esophagectomy (MIE) is being increasing used for surgical resection of esophageal malignancies in the USA. MIE is being safely performed with equivalent technical adequacy and short-term outcomes when compared to open esophagectomy. MIE may be associated with a slightly shorter hospital length of stay compared to open esophagectomy.